2016
DOI: 10.3126/jmmihs.v2i0.15789
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Hospital Based Study In Kathmandu to Assess the Seroprevalence of Hepatitis B Virus

Abstract: BackgroundHepatitis B is a major public health issue in Nepal. Acute as well chronic Hepatitis B infection can lead to different hepatic manifestation ranging from acute liver failure, aplastic anemia and liver cirrhosis to liver cancer. Although, there is a presence of high burden of viral hepatitis in Nepal but little have been studied about it. So this study was aimed to obtain the seroprevalence of Hepatitis B among all the patients: outpatient as well as patient in different wards visiting a tertiary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…When the percentages between males and females among 300 samples were compared, 244 samples (81.3%) were male and 56 samples (18.7%) were female (male:female ratio, 4.4:1). This is similar to other studies from Nepal by Gupta et al, Shrestha et al and Bhatta et al reporting high male-to-female ratios of HBV infection (2.5:1, 3.2:1, 9.0:1, respectively) [ 17 19 ]. The high male-to-female ratios of HBV infection have also been reported in recent epidemiological studies in Ghana (2.2:1), China (1.5:1), and Pakistan (2.1:1) as well as retrospective data of 1982–1998 in the USA (1.8:1) [ 20 – 23 ].…”
Section: Hbv Epidemiology In Nepal Compared With Other Developing Countriessupporting
confidence: 92%
“…When the percentages between males and females among 300 samples were compared, 244 samples (81.3%) were male and 56 samples (18.7%) were female (male:female ratio, 4.4:1). This is similar to other studies from Nepal by Gupta et al, Shrestha et al and Bhatta et al reporting high male-to-female ratios of HBV infection (2.5:1, 3.2:1, 9.0:1, respectively) [ 17 19 ]. The high male-to-female ratios of HBV infection have also been reported in recent epidemiological studies in Ghana (2.2:1), China (1.5:1), and Pakistan (2.1:1) as well as retrospective data of 1982–1998 in the USA (1.8:1) [ 20 – 23 ].…”
Section: Hbv Epidemiology In Nepal Compared With Other Developing Countriessupporting
confidence: 92%
“…10,13 In a study done in Kathmandu city of Nepal by Bhatta et al, showed the prevalence rate of 4.19% which was a little higher than our study. 14 In our study, only 506 (29.7%) males participated as compared to females 1198 (70.3%) which shows the deep root of illiteracy and lack of public awareness in the society. Males had a higher prevalence rate (4.34%) as compared to female participants (2.58%).…”
Section: Discussionmentioning
confidence: 59%
“…A sero positivity of 1.10% and 0.58% was reported amongst the hospital attendees from Warudi in Nashik, (20) and Tumkuru, South India (21) . On the contrary, in a retro-prospective study conducted at a hospital in Nepal and a tertiary care hospital at North Western Nigeria seroprevelance of 4.19% (22) and 9.2% (23) has been reported. In another pivotal study conducted at a North Indian Hospital from 2005-2013 seroprevelance was found to range from 0.92% to 1.75% (24) indicative of consistent infection.…”
Section: Resultsmentioning
confidence: 89%
“…Similar to our study, a maximum seropositivity was reported in the age group of 41-60 (41.6%) years as compared to the younger age group from south India (21) also. In the neighbouring country of Nepal the highest prevalence (30%) of HBsAg was reported among the age group of 51-60 years (22) and depicted as the most susceptible group. In yet another study a maximum seroprevalence (53.63% and 50.0%) was reported in the age group of 30-40 and 40-50 respectively (39) .…”
Section: Resultsmentioning
confidence: 93%